Ethyl 4-[(3,5-di-tert-butyl-2hydroxybenzylidene)amino]benzoata - Shakir, R.M.; Ariffin, A.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, a Schiff base, C24H31NO3, has a substituted aromatic ring at both ends of the azomethine linkage and these make a dihedral angle of 24.9 (1)degrees. There is an intramolecular hydrogen bond between the hydroxy group (donor) and the N atom of themazomethine linkage.